Inequalities in Health in a Municipality in Serbia - Simović, Tatjana; Radojlovic, Jasmina Ruse; Memić, Mensur (Vojnosanitetski pregled, 2020)
Background/Aim. A consistent association between socioeconomic determinants and health related variables has been found in many European countries. The aims of this study were: to analyze the association of socioeconomic factors with self-perceived health and utilization of health services as well as to suggest some interventions to overcome the existing problems. Methods. Hybrid study was pefrormed. The two cross-sectional studies were conducted on quota samples (1999 and 2015) in Kruševac Municipality. The questionnaire was used as the investigation instrument for 196 interviewees in 1999 and 226 interviewees in 2015. Results. In the reporting period, there were the following results: a significant increase in people who did not have a steady income (χ2 = 22.800; df = 4; р
Keywords: health status; socioeconomic factors; health services; serbia